2021
DOI: 10.3390/nano11030779
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Silica Star-Shaped Nanoparticles and Human Mesenchymal Stem Cells: An In Vitro Model

Abstract: The biomedical translational applications of functionalized nanoparticles require comprehensive studies on their effect on human stem cells. Here, we have tested neat star-shaped mesoporous silica nanoparticles (s-MSN) and their chemically functionalized derivates; we examined nanoparticles (NPs) with similar dimensions but different surface chemistry, due to the amino groups grafted on silica nanoparticles (s-MSN-NH2), and gold nanoseeds chemically adsorbed on silica nanoparticles (s-MSN-Au). The different sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 91 publications
2
12
0
Order By: Relevance
“…More experiments are necessary to explain the mechanism. In conclusion, in accordance with our previous works, all these data confirmed that the two types of stem cells used exhibit a different interaction and behaviour on the same film surface [ 57 , 72 ].…”
Section: Resultssupporting
confidence: 92%
“…More experiments are necessary to explain the mechanism. In conclusion, in accordance with our previous works, all these data confirmed that the two types of stem cells used exhibit a different interaction and behaviour on the same film surface [ 57 , 72 ].…”
Section: Resultssupporting
confidence: 92%
“…To obtain FITC-labeled MSN, amino-conjugated nanoparticles (NH 2 -MSN) were synthesized according to the literature [33]. Briefly, 100 mg MSN was dispersed in 50 mL methanol after 30 min of ultrasound treatment.…”
Section: Synthesis Of Fitc-labeled Msn and Ha-msnmentioning
confidence: 99%
“…Immunofluorescences were performed according to our previous work [ 28 , 29 , 30 ]. Briefly, cells seeded on glass coverslips at the optimal density of 1 × 10 3 were fixed with 4% paraformaldehyde, permeabilized, blocked in PBS + 10% FBS, 0.1% Triton X-100 for 1 h at RT, and incubated overnight at 4 °C with the primary antibody, that based on the analyses were: anti-collagen I (COL.1) (1:300, Chemicon International, Temecula, CA, USA) and anti-collagen III (1:300, COL.3 Chemicon International, Temecula, CA, USA); anti-SOD1 (1:400, Santa Cruz Biotechnology, CA, USA).…”
Section: Methodsmentioning
confidence: 99%